The Far-Infrared Radio Correlation at low radio frequency with LOFAR/H-ATLAS . Issue 4 (13th August 2018) - Read, S C; Smith, D J B; Gürkan, G; Hardcastle, M J; Williams, W L; Best, P N; Brinks, E; Calistro-Rivera, G; Chyży, K T; Duncan, K; Dunne, L; Jarvis, M J; et al.
ABSTRACT: The radio and far-infrared luminosities of star-forming galaxies are tightly correlated over several orders of magnitude; this is known as the far-infrared radio correlation (FIRC). Previous studies have shown that a host of factors conspire to maintain a tight and linear FIRC, despite many models predicting deviation. This discrepancy between expectations and observations is concerning since a linear FIRC underpins the use of radio luminosity as a star-formation rate indicator. Using LOFAR $\mathrm{150\, MHz}$ , FIRST $\mathrm{1.4\, GHz}$ , and Herschel infrared luminosities derived from the new LOFAR/ H -ATLAS catalogue, we investigate possible variation in the monochromatic ( $\mathrm{250\, μ}$ m) FIRC at low and high radio frequencies. We use statistical techniques to probe the FIRC for an optically selected sample of 4082 emission-line classified star-forming galaxies as a function of redshift, effective dust temperature, stellar mass, specific star formation rate, and mid-infrared colour (an empirical proxy for specific star formation rate). Although the average FIRC at high radio frequency is consistent with expectations based on a standard power-law radio spectrum, the average correlation at $\mathrm{150\, MHz}$ is not. We see evidence for redshift evolution of the FIRC at $\mathrm{150\, MHz}$, and find that the FIRC varies with stellar mass, dust temperature, and specific star formation rate, whether the latter is probed using magphys fitting, or using mid-infrared colour as a proxy. We can explain the variation, to within 1σ, seen in the FIRC over mid-infrared colour by a combination of dust temperature, redshift, and stellar mass using a Bayesian partial correlation technique.